ANAK SEBAGAI AMANAH DARI ALLAH - Idris, Idris (Musawa: Journal for Gender Studies, 2019)
Mandate in the Qur'an is a duty that must be maintained by Muslims and by always asking for help from Allah SWT in order to maintain that mandate. Mandate has a broad meaning, including a variety of understandings, but the substance is that people must have a sense of responsibility for what is assumed on their shoulders. Aware that everything will be accounted before the God. Children are the gifts of Allah SWT that should be guarded, nurtured, guided, educated and also must to develop all of their potential according to their nature. On the other hand, children are the next generation of the coreligionists. Children are the most beautiful gift from god and at once be a trust (entrusted) that Allah SWT gives to every parents. Therefore, parents should be care to the needs and development of their children, so that they could be grow into healthy children, both physically and spiritually, and Berakhlaqul karimah and have a high intelligence. That how great the role of the next generation to the success of a Nation. Education of children has gained top priority. Because education is a very important factor in changing a civilization, so education cannot be separated from life. When someone blessed with a child then she/he has an obligation to fulfill the rights of the child, that was described by the Prophet in a hadith contained in the book of Tanbih al-Ghafilin. Narrated from Abu Hurairah RA The Prophet actually said: "there are three rights of the child to his/her parents; given a good name at birth, taught the Qur'an when it is intelligent (tamyiz) and married when it has found".